Effect of organic additives on silver release from nanosilver–polyethylene composite films to acidic food simulant. (1st August 2017) - Su, Qi-Zhi; Lin, Qin-Bao; Chen, Chao-Fang; Wu, Li-Bing; Wang, Zhi-Wei
Highlights: Organic additives have two effects on silver release from nanosilver–PE films. Reactions between organic additives and silver promote silver release. Additives can promote or inhibit silver release by affecting silver oxidation. High temperature and humidity film treatment promotes silver release. Abstract: The effects of organic additives (Irgafos 168, Irganox 1076, Tinuvin 622, Chimassorb 944, UV-P, and UV-531) on silver release from nanosilver–polyethylene composite films into an acidic food simulant (3% acetic acid) were investigated using inductively coupled plasma mass spectrometry. The limits of detection and quantification, coefficient of determination, and recoveries of the method used were 3.7 ng L –1, 12.4 ng L –1, 0.999, and 89–113%, respectively. The results indicated that additives can affect silver release via two simultaneous processes: (i) reactions between organic additives and silver that promote silver release from the composite film to the acidic food simulant; and (ii) the promotion or inhibition of silver release by affecting silver oxidation. High temperature and humidity treatment of the composite films was found to significantly increase silver release by promoting silver oxidation.